Chemical stability of carbon pool in peatlands dominated by different plant types in Jilin province (China) and its potential influencing factors - Cong, Jinxin; Gao, Chuanyu; Zhao, Haiyang; Han, Dongxue; Meng, Fang; Wang, Guoping (Frontiers in Ecology and Evolution, 2023)
The peat carbon pool stores 30% of the total global soil carbon accounting for 3–4% of the global land surface. The stability of the peatland carbon pool is a key factor affecting global carbon cycling that is seriously disturbed by climate change and regional human activities. However, the impact of these factors on carbon pool stability remains poorly understood. Based on the physicochemical properties and carbon compounds of 973 peat samples from Jilin Province (China), which are widely distributed in different altitude regions of the Changbai Mountains, we investigated the stability of the carbon pool in different dominant plants and degradation types of peatlands and assessed the effects of regional environmental factors on the peatland carbon pool. Our results showed that the carbohydrate content of peat soils in different peatland types ranged from 33.18±6.90% to 40.51±4.80%, and the aromatic content ranged from 19.77±1.15% to 22.69±2.30%. Bulk density is the most important physicochemical factor, and annual average temperature is the most important environmental factor that influences carbon stability. The effects of selected environmental factors on the peatland carbon pool covered by different plants vary, and the carbon stability in shrub peatlands is more sensitive to climate characteristics than in peatlands dominated by the other two plant types. Peatland degradation decreases the carbon stability in herb and herb/shrub peatlands and increases the carbon stability in shrub peatlands, leading the peatland carbon pool to be more easily influenced by regional human activities than natural peatlands.